2022
DOI: 10.1037/dhe0000299
|View full text |Cite
|
Sign up to set email alerts
|

What are we saying by saying so little? Mission statements, diversity mission statements, and NCAA programs.

Abstract: Prior research has analyzed the purpose and composition of athletic mission statements, but no prior work has moved beyond athletic mission statements and toward athletic diversity mission statements. Specifically, this study sought to understand the prevalence of both athletic mission and diversity mission statements and how National Collegiate Athletic Association (NCAA) programs address diversity in both types of statements. Through a content analysis of 250 NCAA websites from both public and private instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…With respect to private/public institutions, private institutions may have more freedom and flexibility in developing and implementing diversity-related policies. This finding is also consistent with Ortega et al (2022). They investigated the presence, and content, of athletics mission statements and diversity mission statements in NCAA athletic departments, and while they found that departments in public institutions were more likely to have a specific diversity mission statement, the explicit inclusion of sexual orientation was more likely to occur in statements developed by private institutions.…”
Section: Contributionssupporting
confidence: 71%
See 2 more Smart Citations
“…With respect to private/public institutions, private institutions may have more freedom and flexibility in developing and implementing diversity-related policies. This finding is also consistent with Ortega et al (2022). They investigated the presence, and content, of athletics mission statements and diversity mission statements in NCAA athletic departments, and while they found that departments in public institutions were more likely to have a specific diversity mission statement, the explicit inclusion of sexual orientation was more likely to occur in statements developed by private institutions.…”
Section: Contributionssupporting
confidence: 71%
“…Other private schools without a strong evangelical base, howeversuch as Northeastern University or Stanfordmay have more leeway than public schools to promote inclusion initiatives. With relevance to this discussion Ortega et al (2022) examined athletic department diversity mission statements. Though public institutions were more likely to publish a diversity statement, private schools were more likely than public schools to explicitly mention sexual orientation in such a statement.…”
Section: Ijsms 243mentioning
confidence: 99%
See 1 more Smart Citation
“…One way this problem has been investigated is through analyses of DEI statements from sport organizations and athletic departments. For example, Ortega et al (2020) examined athletic department mission statements and found that only 29 of 250 athletic departments (11.6%) had diversity-specific mission statements. The racially-charged events of the of summer 2020 transformed this commitment, as we have seen a dramatic increase in public statements, along with the creation of diversity committees, the renaming of buildings, and removal of statues honoring individuals with racist pasts (Turick et al, 2020) -yet these outward-facing DEI initiatives were seen as reactionary rather than proactive (Hylton, 2020).…”
Section: Diversity Equity and Inclusion In Sport Organizationsmentioning
confidence: 99%
“…Deephouse goes further by arguing that mission statements also serve crucial internal and external roles. To date, the vast spectrum of existing studies in mission statement research explores important topics such as the influence of organizational size (O'Gorman and Doran, 1999; King et al , 2014a, b); corporate identity (Leuthesser and Kohli, 1997, 2015); the reflection of trends in ethics and corporate social responsibility (Jung and Pompper, 2014; King et al , 2010; Wilburn and Wilburn, 2014, 2015; Fifka et al , 2018); global initiatives and international comparative analysis (Mion et al , 2021; King et al , 2011, 2014b; Mas-Machuca et al , 2017; Panda and Gupta, 2003; Sengupta and Sahay, 2017); the importance of stakeholder representation (Bartkus and Glassman, 2008); the link between organizational performance and effective mission statements (Atrill et al , 2005; Bart and Baetz, 2002; Baetz and Kenneth, 1998; Bart et al , 2001; Bart and Hupfer, 2004; Ekpe et al , 2015; Germain and Cooper, 1990; Green and Medlin, 2003; value creation (Zerfass and Viertmann, 2017); member motivation and implementation (Rey and Bastons, 2018) and ensuring diversity, equity, and inclusion in organizational mission statements (Swenor and Meeks, 2019; Ortega et al , 2020). The breadth of existing mission research also spans a broad cross-section of specific industries and sectors including research of mission statements for commercial airlines (Law and Breznik, 2018; Kemp and Dwyer, 2003); cruise lines (Penco et al , 2017); health-care organizations (Bart, 2002; Bart and Hupfer, 2004, Kamran and Cin, 2020); educational services organizations and institutions (Bayrak, 2020; Yob et al , 2016; Lineham, 2013; Woodrow, 2006; Davis et al , 2007; Genç, 2012; Palmer and Short, 2008); non-profit organizations (Bart, 2000; Macedo et al , 2016; Pandey et al , 2017; Kirk and Nolan, 2010; Sheehan, 1996); public organizations (Desmidt, 2016) and philanthropic organizations (Kesberg and Keller, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%